Information Resilience in Networks : An Analysis of a National Security Legislation Evidence Base - Rantamäki, Aino; Uusikylä, Petri; Jalonen, Harri (Umeå University, 2023)
Governance theory emphasises that networks are pivotal to societal governance and related steering mechanisms. One important means of steering is legislation, the evidence base of which is built on the interaction between social actors and the expert hearings related to the legislative process. This research uses network analysis to examine the construction of a legislative knowledge base and the information resilience displayed in the related networks. The data are derived from experts (n=440) appearing in committee hearings on five proposed acts of parliament. The results show that the expert consultations behind the legislation are official-oriented and illuminate the limited information produced by the private sector and a narrow view of scientific expertise. The network reveals epistemic authorities – mainly representing the security cluster – acting as gatekeepers. A more systemic approach is needed to build an evidence base encompassing the views on societal phenomena derived from different disciplines.
Keywords: information resilience; epistemic governance; knowledge regime; social network analysis; legislation; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|